2020
DOI: 10.1002/ccd.28736
|View full text |Cite
|
Sign up to set email alerts
|

Impact of extended dual antiplatelet therapy on clinical prognosis in acute coronary syndrome patients with intermediate or high ischemic risk defined by the GRACE score

Abstract: Objectives To evaluate the impact of extended dual antiplatelet therapy (DAPT) beyond 12 months in acute coronary syndrome (ACS) patients with intermediate‐risk to high‐risk of developing ischemia according to the Global Acute Coronary Event Registration (GRACE) score. Background The duration of optimal DAPT remains controversial in patients at higher risk of developing ischemia. Methods Overall, 9,309 ACS patients in the Optimal antiPlatelet Therapy for Chinese patients with Coronary Artery Disease (OPT‐CAD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Several previous studies demonstrated that elderly patients with ACS are at higher risk of recurrent NACCE compared to younger patients (2,15,16). Previously, Bian et al conducted a study to evaluate the optimal antiplatelet therapy for Chinese patients with coronary artery disease (OPT-CAD) which showed a lower incidence of net adverse clinical events in the DAPT group than the single antiplatelet therapy group (17). Furthermore, subgroup analysis based on the Global Registration of Acute Coronary Events (GRACE) score revealed that the net adverse clinical outcomes of continued DAPT were not significantly different in terms of age [relative risk (RR) (95% CI): ≥65: 0.54 (0.33-0.88), <65: 0.75 (0.29-1.92), P for interaction =0.54] (17).…”
Section: Validation Of the Bric-acs Scorementioning
confidence: 99%
“…Several previous studies demonstrated that elderly patients with ACS are at higher risk of recurrent NACCE compared to younger patients (2,15,16). Previously, Bian et al conducted a study to evaluate the optimal antiplatelet therapy for Chinese patients with coronary artery disease (OPT-CAD) which showed a lower incidence of net adverse clinical events in the DAPT group than the single antiplatelet therapy group (17). Furthermore, subgroup analysis based on the Global Registration of Acute Coronary Events (GRACE) score revealed that the net adverse clinical outcomes of continued DAPT were not significantly different in terms of age [relative risk (RR) (95% CI): ≥65: 0.54 (0.33-0.88), <65: 0.75 (0.29-1.92), P for interaction =0.54] (17).…”
Section: Validation Of the Bric-acs Scorementioning
confidence: 99%